2017
DOI: 10.1186/s12939-017-0549-3
|View full text |Cite
|
Sign up to set email alerts
|

Critical race theory as a tool for understanding poor engagement along the HIV care continuum among African American/Black and Hispanic persons living with HIV in the United States: a qualitative exploration

Abstract: BackgroundAfrican American/Black and Hispanic persons living with HIV (AABH-PLWH) in the U.S. evidence insufficient engagement in HIV care and low uptake of HIV antiretroviral therapy, leading to suboptimal clinical outcomes. The present qualitative study used critical race theory, and incorporated intersectionality theory, to understand AABH-PLWH’s perspectives on the mechanisms by which structural racism; that is, the macro-level systems that reinforce inequities among racial/ethnic groups, influence health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(101 citation statements)
references
References 60 publications
0
100
0
1
Order By: Relevance
“…The lack of attention to the relationship context, especially for women who are often disempowered in their intimate partnerships with men, prompted the development of the Theory of Gender and Power [42]. Finally, some critics have cited the theories’ limited relevance for ethnic/racial minorities and called for greater use of Critical Race Theory [4345]. …”
Section: What Are the Major Health Behavioral Theories?mentioning
confidence: 99%
“…The lack of attention to the relationship context, especially for women who are often disempowered in their intimate partnerships with men, prompted the development of the Theory of Gender and Power [42]. Finally, some critics have cited the theories’ limited relevance for ethnic/racial minorities and called for greater use of Critical Race Theory [4345]. …”
Section: What Are the Major Health Behavioral Theories?mentioning
confidence: 99%
“…As suggested by Critical Race Theory (CRT), this finding is linked to the systemic structural underpinning of mental health treatment barriers to depression among AA populations [45,46]. On an institutional level, treatment disparities for older AAs are linked to structural racism and discrimination, cultural mistrust, provider stereotypes and bias [62].…”
Section: Discussionmentioning
confidence: 99%
“…AA's health risk behaviors may be indirect effects of structural factors, as posited by CRT. Treatment for depression provided by health care providers should involve consideration of sociocultural values and preferences, in addition to addressing the manifestations of structural racism rooted within specific health care settings [23,46,69].…”
Section: Discussionmentioning
confidence: 99%
“…Arguably, they may well be an even more vulnerable, and more hidden, population than the newly diagnosed—without highly visible, tailored programs for them. A recent qualitative study by Freeman et al showed that Black and Latino patients living with HIV who were out of care viewed HIV care decisions through the lens of institutional discrimination, which led to feeling pressured to take ART, excluded from shared-decision making, and ignored in terms of other life concerns [ 47 ]. Incorporating a health equity perspective focused on eliminating disparities into the iART intervention must include the perspectives of patients who continually fall out of HIV care.…”
Section: A Health Equity Perspective For Iart: Stigma and Mistrustmentioning
confidence: 99%